Determination of dexamethasone acetate in CETETH 20‐based in liquid crystalline systems using HPLC. (23rd December 2020) - Oyafuso, Márcia Helena; Fonseca‐Santos, Bruno; Kogawa, Ana Carolina; Carvalho, Flávia Chiva; Gremião, Maria Palmira Daflon; Chorilli, Marlus
Abstract: Dexamethasone acetate (DEX), a potent anti‐inflammatory, is used primarily in the treatment of inflammatory and autoimmune diseases. It was incorporated in CETETH 20 (polyoxyethylene 20 cetyl alcohol)–based liquid crystalline systems to enhance the purpose of the drug. Concomitant with the pharmaceutical technology performed, a HPLC method was developed and validated for the quantification of dexamethasone acetate in CETETH 20‐based liquid crystalline systems for the evaluation of the drug in the new matrix. The method was performed using a C18 column with acetonitrile:methanol:water (35:35:30, v/v/v) as the mobile phase at a flow rate of 0.8 mL min −1 at 239 nm. The method was linear in the range of 1–25 μg mL −1 ; the limit of quantification and limit of detection were 0.05 and 0.16 μg mL −1, respectively; the accuracy of the method was 99.92% (relative standard deviation < 1%), and it presented intra‐day and inter‐day precision with deviations less than 1%. In this context, the method was successfully used to determine the incorporation efficiency of DEX in CETETH 20‐based liquid crystalline systems and can be easily used by pharmaceutical companies and laboratories around the world.